A method for preparing a modified silicone resin and heavy-duty anticorrosive powder coating and a method for preparing and use thereof

CN120383733BActive Publication Date: 2026-10-16CHANGSHA TIANYUAN EMPIRE MATERIALS TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510637790.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-16
Publication Date
2026-10-16
Estimated Expiration
2045-05-16

AI Technical Summary

Technical Problem

但是传统的环氧粉末涂料在油田的高温高压动态工况下容易出现“涂层鼓泡-介质渗透-界面剥离”失效链,尤其是对于井深5000米以上深井油田管道(包括油管、采油杆等),其工况条件为:温度150~220℃、压力15~50MPa、H2S/CO2共存腐蚀介质,条件更为苛刻

Benefits of technology

[0027] The results of the examples show that the heavy-duty anti-corrosion powder coating provided by the present invention has an abrasion resistance of ≥2.2 L/μm (sand drop method), adhesion of 5A grade (better than the standard requirement of 3A grade); corrosion resistance: 10% HCl (room temperature, 90 days): no change in coating; 3.5% NaCl (room temperature, 90 days): no change in coating; crude oil (80℃, 90 days): no change in coating; high temperature and high pressure performance: Condition 1: 180℃/70MPa/16h (NaOH solution, pH=12.5), Condition 2: 107℃/35MPa/16h (water/toluene/kerosene mixture), results: no bubbles in the coating, adhesion maintained at 5A grade. Furthermore, the heavy-duty anti-corrosion powder coating, after high temperature and high pressure simulation test at 220℃/35MPa H2S saturated aqueous solution (720h), showed no bubbling and an adhesion grade of 1, demonstrating excellent long-term protective performance under extreme working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120383733B_ABST
    Figure CN120383733B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of modified silicone resin and heavy-duty anticorrosive powder coating and a preparation method and application thereof, and relates to the technical field of functional coating.The modified silicone resin prepared by the application is a special dicyandiamide-curable silicone resin, which is compounded with epoxy resin and linear phenolic epoxy resin as main film-forming materials of the coating, and modified dicyandiamide is used as a curing agent, so that the acid boiling resistance and high-temperature resistance of the epoxy powder coating can be greatly improved, and the long-acting protection performance of the epoxy powder coating under extreme working conditions of high temperature and high pressure can be significantly improved.The application provides a heavy-duty anticorrosive powder coating, and the heavy-duty anticorrosive powder coating provided by the application is a wear-resistant and anticorrosive integrated coating with excellent interface bonding performance, and is particularly suitable for long-acting protection of oilfield pipelines under working conditions of high temperature, high pressure and strong corrosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional coatings technology, and in particular to a method for preparing a modified organosilicon resin and a heavy-duty anti-corrosion powder coating, as well as the preparation method and application thereof. Background Technology

[0002] Corrosion protection of downhole oil pipes in oil and gas fields plays a vital role in the petroleum industry. It can extend the service life of oil pipes, improve production efficiency, and ensure the safe transportation of oil and gas.

[0003] Epoxy powder coatings are among the most commonly used anti-corrosion materials for oil pipelines. Traditional epoxy powder coatings are typically prepared by combining one or more of epoxy resin, polyester resin, acrylic resin, and phenolic resin, with the addition of pigments, fillers, and functional additives. However, traditional epoxy powder coatings are prone to a "coating blistering-medium penetration-interface peeling" failure chain under the high-temperature and high-pressure dynamic conditions of oilfields, especially for deep-well oilfield pipelines (including tubing and production rods) at depths of over 5000 meters, where the operating conditions are: temperature 150–220℃, pressure 15–50 MPa, and H2S / CO2 coexisting corrosive media, making the conditions even more demanding. Traditional epoxy powder coatings struggle to meet the long-term protective performance requirements under extreme conditions. Summary of the Invention

[0004] In view of this, the purpose of this invention is to provide a method for preparing a modified silicone resin and a heavy-duty anti-corrosion powder coating, as well as the preparation method and application thereof. The modified silicone resin prepared by this invention is beneficial for improving the long-term protective performance of epoxy powder coatings under extreme high-temperature and high-pressure conditions.

[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution:

[0006] This invention provides a method for preparing a modified organosilicon resin, comprising the following steps:

[0007] Methyltrimethoxysilane, phenyltriethoxysilane, and isocyanate-propyltriethoxysilane are mixed with an alcohol-water solvent and subjected to hydrolysis and polycondensation to obtain a solution containing isocyanate-terminated polysiloxanes; the hydrolysis and polycondensation are carried out under conditions of pH 3 to 6;

[0008] The solution containing the terminal isocyanate polysiloxane was mixed with dicyandiamide and amino-entrained cage-type silsesquioxane to carry out a hybrid crosslinking polycondensation reaction to obtain a solution containing Si, O, C and N hybrid crosslinked polymers.

[0009] The modified organosilicon resin is obtained by removing the solvent from the solution containing the Si, O, C and N hybrid crosslinked polymer.

[0010] Preferably, by mass parts, the methyltrimethoxysilane is 60-80 parts, the phenyltriethoxysilane is 20-40 parts, the isocyanate-propyltriethoxysilane is 15-25 parts, the dicyandiamide is 10-20 parts, and the amino-coated cage-type silsesquioxane is 5-10 parts.

[0011] Preferably, the hydrolysis condensation temperature is 50–80°C and the time is 2–4 h; the hybrid crosslinking condensation reaction temperature is 60–100°C and the time is 2–6 h.

[0012] This invention provides a heavy-duty anti-corrosion powder coating, comprising the following raw materials in weight percentages:

[0013] The composition includes: 15-35% epoxy resin, 5-15% linear phenolic epoxy resin, 15-25% modified silicone resin, 2-5% graphene-modified silicon-titanium nanopolymer slurry, 15-25% wear-resistant reinforcing filler, 1-10% mica powder, 0.5-2% pigment, 0.1-0.3% hydrophobic interface modifier, 0.1-1% fumed silica, 5-15% silica powder, 0.5-1.5% dispersant, 0.5-1.5% wetting agent, 0.5-1.5% defoamer, 0.4-1.5% conductive agent, 0.5-1.5% adhesion promoter, 0.5-1.5% leveling agent, and 1-5% dicyandiamide curing agent.

[0014] The wear-resistant reinforcing filler includes carbides and / or metal oxides; the hydrophobic interface modifier includes fluorocarbon silane coupling agents and / or modified polysiloxane copolymers; the modified organosilicon resin is the modified organosilicon resin prepared by the preparation method described in the above technical solutions.

[0015] The graphene-modified silicon-titanium nanopolymer slurry comprises the following raw materials in parts by weight: 40-60 parts titanium hydride, 2-5 parts activated silica, 1-2 parts silane coupling agent modified graphene, 10-30 parts silicon-modified epoxy resin, 3-6 parts reactive diluent, 2-10 parts N-methylpyrrolidone, 1-5 parts dispersant, 1-5 parts coupling agent, 0.01-0.1 parts catalyst, 0.1-0.2 parts wetting agent, and 0.1-0.2 parts wetting aid.

[0016] Preferably, the epoxy equivalent of the epoxy resin is 600 to 1800.

[0017] Preferably, the carbide includes one or more of silicon carbide, titanium carbide, and tungsten carbide; the metal oxide includes zirconium oxide and / or ceramic alumina.

[0018] Preferably, the fluorocarbon silane coupling agent comprises heptadecafluorodecyltriethoxysilane coupling agent, and the modified polysiloxane copolymer comprises polyether siloxane.

[0019] Preferably, the particle size of the heavy-duty anti-corrosion powder coating is less than 70 micrometers, and the mass percentage of particles with a particle size of less than 50 micrometers is ≥80%.

[0020] This invention provides a method for preparing the heavy-duty anti-corrosion powder coating described above, comprising the following steps:

[0021] Graphene-modified silicon-titanium nanopolymer slurry is premixed with a hydrophobic interface modifier to form a hydrophobic premixed slurry.

[0022] The hydrophobic premixed slurry is mixed with wear-resistant reinforcing filler to form a core-shell structured slurry.

[0023] The core-shell structure slurry is mixed with epoxy resin, linear phenolic epoxy resin, modified organosilicon resin, pigment, mica powder, fumed silica, silica powder, dispersant, wetting agent, defoamer, conductive agent, adhesion promoter, leveling agent and dicyandiamide curing agent. The resulting mixture is melt-extruded and then powdered to obtain the heavy-duty anti-corrosion powder coating.

[0024] This invention provides the application of the heavy-duty anti-corrosion powder coating described in the above technical solutions or the heavy-duty anti-corrosion powder coating prepared by the above technical solutions in the corrosion protection of oilfield pipelines.

[0025] This invention provides a method for preparing modified organosilicon resin. First, methyltrimethoxysilane, phenyltriethoxysilane, and isocyanate-propyltriethoxysilane are hydrolyzed and condensed to form isocyanate-terminated polysiloxane. The methyltrimethoxysilane, phenyltriethoxysilane, and isocyanate-propyltriethoxysilane combine hardness, flexibility, and heat resistance. Furthermore, the isocyanate groups in the formed isocyanate-terminated polysiloxane bridge dicyandiamide and amino-modified cage-like silsesquioxane (NH2-POSS) to form a hybrid network. This structure solves the problem of poor compatibility between dicyandiamide and the resin, and also results in a high crosslinking density (over 95%) after organosilicon curing, leading to excellent temperature and pressure resistance. The introduction of the NH2-POSS nano-reinforcing structure further inhibits thermal oxidative degradation. The modified silicone resin prepared by this invention is a special silicone resin that can be cured by dicyandiamide. After curing, the resin has a thermal decomposition temperature of over 480℃ and the coating remains intact under a high temperature test of 600℃ / 100h (GB / T 1735-2009). When combined with epoxy resin and linear phenolic epoxy resin as the main film-forming substance of the coating, and using a dicyandiamide curing agent, it can significantly improve the acid resistance and high temperature resistance of epoxy powder coating, and significantly improve the long-term protective performance of epoxy powder coating under extreme high temperature and high pressure conditions.

[0026] This invention provides a heavy-duty anti-corrosion powder coating, comprising the following raw materials in the indicated weight percentages: 15-35% epoxy resin, 5-15% linear phenolic epoxy resin, 15-25% modified organosilicon resin, 2-5% graphene-titanium silicon nano-slurry, 15-25% wear-resistant reinforcing filler, 1-10% mica powder, 0.5-2% pigment, 0.1-0.3% hydrophobic interface modifier, 0.1-1% fumed silica, 5-15% silica fume, 0.5-1.5% dispersant, 0.5-1.5% wetting agent, 0.5-1.5% defoamer, 0.4-1.5% conductive agent, 0.5-1.5% adhesion promoter, 0.5-1.5% leveling agent, and 1-5% dicyandiamide curing agent. In this invention, the modified organosilicon resin is a dicyandiamide-curable organosilicon specialty resin, which, when combined with epoxy resin and linear phenolic epoxy resin, serves as the main film-forming substance in the coating, significantly improving the high-temperature resistance of the coating while retaining the excellent adhesion and chemical resistance of epoxy and phenolic resins. The hydrophobic interface modifier can coat the solid particles in the graphene-modified silicon-titanium nanopolymer slurry; the resin and coupling agent in the graphene-modified silicon-titanium nanopolymer slurry can also be adsorbed and anchored to the surface of the wear-resistant reinforcing filler to form a core-shell structure. This invention not only ensures the crosslinking properties of the shell and the main resin in the powder coating formulation during dicyandiamide curing, but also optimizes the dispersion and stability of the hard-phase wear-resistant components. This guarantees both ultra-high density and excellent hardening and wear resistance of the coating. Simultaneously, the hydrophobic interface modifier improves the overall hydrophobicity of the coating, enhancing its resistance to water and the ability to resist the wetting and penetration of various acid, alkali, and salt ions in water. The graphene-modified silicon-titanium nanopolymer slurry also contains crosslinkable epoxy groups, which can simultaneously participate in the crosslinking of the curing agent with other resins in the powder coating, improving strength and density. The heavy-duty anti-corrosion powder coating provided by this invention is an integrated wear-resistant and anti-corrosion coating with excellent interfacial bonding performance, enabling long-term protection under extreme working conditions.

[0027] The results of the examples show that the heavy-duty anti-corrosion powder coating provided by the present invention has an abrasion resistance of ≥2.2 L / μm (sand drop method), adhesion of 5A grade (better than the standard requirement of 3A grade); corrosion resistance: 10% HCl (room temperature, 90 days): no change in coating; 3.5% NaCl (room temperature, 90 days): no change in coating; crude oil (80℃, 90 days): no change in coating; high temperature and high pressure performance: Condition 1: 180℃ / 70MPa / 16h (NaOH solution, pH=12.5), Condition 2: 107℃ / 35MPa / 16h (water / toluene / kerosene mixture), results: no bubbles in the coating, adhesion maintained at 5A grade. Furthermore, the heavy-duty anti-corrosion powder coating, after high temperature and high pressure simulation test at 220℃ / 35MPa H2S saturated aqueous solution (720h), showed no bubbling and an adhesion grade of 1, demonstrating excellent long-term protective performance under extreme working conditions.

[0028] This invention provides a method for preparing the heavy-duty anti-corrosion powder coating described above. The invention employs a multi-stage dispersion design. First, a hydrophobic interface modifier can coat the solid particles in the graphene-modified silicon-titanium nanopolymer slurry to form a hydrophobic premixed slurry. Furthermore, the hydrophobic interface modifier has good compatibility with the coupling agent in the slurry and can cross-link with each other, making the hydrophobic interface modifier less prone to migration. Then, the hydrophobic premixed slurry is mixed with wear-resistant reinforcing filler. The resin and coupling agent in the graphene-modified silicon-titanium nanopolymer slurry are adsorbed and anchored on the surface of the wear-resistant reinforcing filler to form a core-shell structure, effectively improving the multiphase compatibility and density of the coating. Simultaneously, the hydrophobic interface modifier and the graphene-titanium nanopolymer slurry are more evenly distributed among the hard phase particles of the coating.

[0029] This invention provides the application of the heavy-duty anti-corrosion powder coating described in the above technical solutions or the preparation method described in the above technical solutions in the corrosion protection of oilfield pipelines. The heavy-duty anti-corrosion powder coating provided by this invention is particularly suitable for long-term protection of oilfield pipelines under high temperature, high pressure, and strong corrosive conditions. Attached Figure Description

[0030] Figure 1 The images are electron microscope (EM) images of ordinary epoxy powder coating after abrasion resistance test (a) and heavy-duty anti-corrosion powder coating obtained in Comparative Example 1 after abrasion resistance test (b).

[0031] Figure 2 The images show electron microscope (EM) images of ordinary powder coatings after abrasion resistance testing (a) and heavy-duty anti-corrosion powder coatings obtained by multi-stage dispersion in Example 1 after abrasion resistance testing (b).

[0032] Figure 3 The appearance of the heavy-duty anti-corrosion powder coating obtained by multi-stage dispersion in Example 1. Detailed Implementation

[0033] This invention provides a method for preparing a modified organosilicon resin, comprising the following steps:

[0034] Methyltrimethoxysilane, phenyltriethoxysilane, and isocyanate-propyltriethoxysilane are mixed with an alcohol-water solvent and subjected to hydrolysis and polycondensation to obtain a solution containing isocyanate-terminated polysiloxanes; the hydrolysis and polycondensation are carried out under conditions of pH 3 to 6;

[0035] The solution containing the terminal isocyanate polysiloxane was mixed with dicyandiamide and amino-entrained cage-type silsesquioxane to carry out a hybrid crosslinking polycondensation reaction to obtain a solution containing Si, O, C and N hybrid crosslinked polymers.

[0036] The modified organosilicon resin is obtained by removing the solvent from the solution containing the Si, O, C and N hybrid crosslinked polymer.

[0037] Unless otherwise specified, all raw materials involved in this invention are commercially available products well known in the art.

[0038] In this invention, methyltrimethoxysilane (MTMS), phenyltriethoxysilane (PTES), and isocyanate-propyltriethoxysilane (IPTS) are mixed with an alcohol-water solvent and subjected to hydrolysis and polycondensation to obtain a solution containing terminal isocyanate-terminated polysiloxanes.

[0039] In this invention, the methyltrimethoxysilane, phenyltriethoxysilane, and isocyanate-propyltriethoxysilane can achieve a good balance of hardness, flexibility, and heat resistance in the coating, and give the resulting resin a suitable viscosity. In this invention, the alcohol in the alcohol-water solvent is preferably ethanol, and the volume ratio of alcohol to water is preferably 95:5. In this invention, the hydrolysis-condensation is carried out at a pH of 3-6, where the pH can be 3, 4, 4.5, 5, or 6; preferably, methyltrimethoxysilane, phenyltriethoxysilane, and isocyanate-propyltriethoxysilane are added to an alcohol-water solvent with a pH of 3-6 for hydrolysis-condensation. In this invention, the hydrolysis-condensation temperature is preferably 50-80°C, where it can be 50, 60, 70, or 80°C, and the time is preferably 2-4 hours, where it can be 2, 3, or 4 hours; the hydrolysis-condensation is preferably carried out under stirring. The reactions involved in the hydrolysis-condensation process are as follows (Note: the isocyanate group (-NCO) is stable under acidic conditions and does not participate in hydrolysis):

[0040] MTMS hydrolysis: CH3Si(OCH3)3 + 3H2O → CH3Si(OH)3 + 3CH3OH;

[0041] PTES hydrolysis: C6H5Si(OCH2CH3)3 + 3H2O → C6H5Si(OH)3 + 3CH3CH2OH;

[0042] IPTS hydrolysis: (NCO)C3H6Si(OCH2CH3)3 + 3H2O → (NCO)C3H6Si(OH)3 + 3CH3CH2OH;

[0043] Polycondensation stage: Si-O-Si bonds are formed between silanols through dehydration condensation, while isocyanate-based silanols (IPTS hydrolysis products) act as end-capping agents, occupying the ends of the polymer chains.

[0044] After obtaining a solution containing terminal isocyanate-based polysiloxanes, the present invention mixes the solution containing terminal isocyanate-based polysiloxanes with dicyandiamide and aminated cage-like silsesquioxane (or aminated cage-like polysesquioxane, NH2-POSS) to carry out a hybrid crosslinking polycondensation reaction to obtain a solution containing Si, O, C and N hybrid (denoted as Si-OCN hybrid) polymer.

[0045] In this embodiment of the invention, the NH2-POSS was purchased from Xi'an Qiyue Biotechnology Co., Ltd. In this invention, the temperature of the hybrid crosslinking condensation reaction is preferably 60–100°C, but can be 70, 80, or 90°C, and the time is preferably 2–6 hours, but can be 3, 4, or 5 hours. Preferably, in this invention, dicyandiamide and NH2-POSS are added to the solution containing isocyanate-terminated polysiloxanes, and the temperature is raised to 60–100°C to carry out the hybrid crosslinking condensation reaction. The reactions involved in the hybrid crosslinking condensation reaction are as follows:

[0046] Pre-reaction of dicyandiamide (DCD) with isocyanate-based silanes:

[0047] The amino group (-NH2) of dicyandiamide ((NH2)2C=NC≡N) first reacts with the isocyanate group (-NCO) of the terminal isocyanate polysiloxane to form a urea bond (-NH-CO-NH-) bridging structure (R-NH-C(=O)-NH)2C=NC≡N:

[0048] (NH2)2C=NC≡N+2R-NCO→(R-NH-C(=O)-NH)2C=NC≡N (R is the organosilicon part of the silane, such as -C3H6Si(OH)3). This step is the initial chemical bonding between the siloxane skeleton and dicyandiamide, forming an organic-inorganic hybrid precursor. The two amino groups of dicyandiamide preferentially react with the -NCO of the terminal isocyanate polysiloxane, while the terminal cyano group is retained for subsequent condensation with NH2-POSS.

[0049] The amino group of NH2-POSS reacts with the cyano group of dicyandiamide:

[0050] The amino group (-NH2) of NH2-POSS undergoes a nucleophilic addition reaction with the cyano group (-C≡N) in the pre-reaction product to generate POSS with an imine bond (-NH-C=N-). This reaction anchors the POSS nanostructure into the organosilicon resin network through the condensation of the cyano group and the amino group; finally forming a hybrid network containing Si, O, C and N.

[0051] In this invention, the viscosity of the solution containing the Si, O, C and N hybrid polymer is preferably 2000 to 6000 mPa·s, and can be 2500, 3000, 4000 or 5000 mPa·s.

[0052] After obtaining a solution containing a hybrid polymer of Si, O, C and N, the present invention removes the solvent from the solution containing the hybrid polymer of Si, O, C and N to obtain the modified organosilicon resin.

[0053] In this invention, by mass parts, the methyltrimethoxysilane is preferably 60-80 parts, which can be 60, 70 or 80 parts; the phenyltriethoxysilane is preferably 20-40 parts, which can be 20, 30 or 40 parts; the isocyanate-propyltriethoxysilane is preferably 15-25 parts, which can be 15, 20 or 25 parts; the dicyandiamide is preferably 10-20 parts, which can be 10, 15 or 20 parts; and the amino-modified cage-type silsesquioxane is preferably 5-10 parts, which can be 5, 6, 7, 8, 9 or 10 parts.

[0054] In this invention, the solvent removal method can be vacuum distillation, and the vacuum distillation temperature can be 120°C. After solvent removal, the resulting material is preferably pulverized to obtain the modified organosilicon resin in powder form.

[0055] The modified organosilicon resin prepared by this invention is a special organosilicon resin that can be cured by dicyandiamide. It is combined with epoxy resin and linear phenolic epoxy resin as the main film-forming substance of the coating. The dicyandiamide curing agent can significantly improve the acid resistance and high temperature resistance of epoxy powder coating, and significantly improve the long-term protective performance of epoxy powder coating under extreme high temperature and high pressure conditions.

[0056] This invention provides a heavy-duty anti-corrosion powder coating, comprising the following raw materials in weight percentages:

[0057] The composition includes: 15-35% epoxy resin, 5-15% linear phenolic epoxy resin, 15-25% modified silicone resin, 2-5% graphene-titanium silicon nano-slurry, 15-25% wear-resistant reinforcing filler, 1-10% mica powder, 0.5-2% pigment, 0.1-0.3% hydrophobic interface modifier, 0.1-1% fumed silica, 5-15% silica powder, 0.5-1.5% dispersant, 0.5-1.5% wetting agent, 0.5-1.5% defoamer, 0.4-1.5% conductive agent, 0.5-1.5% adhesion promoter, 0.5-1.5% leveling agent, and 1-5% dicyandiamide curing agent.

[0058] The wear-resistant reinforcing filler includes carbides and / or metal oxides; the hydrophobic interface modifier includes fluorinated silane coupling agents and / or modified polysiloxane copolymers; the modified organosilicon resin is the modified organosilicon resin prepared by the preparation method described in the above technical solutions.

[0059] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by this invention, by weight percentage, include 15-35% epoxy resin, which can be 20%, 30%, 33%, or 34%. In this invention, the epoxy equivalent of the epoxy resin is preferably 600-1800, which can be 600-650, 700-750, 780-850, or 1500-1800. Selecting the above-mentioned epoxy resin is beneficial for balancing melt viscosity, reactivity, and coating toughness.

[0060] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by this invention, by weight percentage, include 5-15% linear phenolic epoxy resin, which can be 7%, 8%, or 10%. In this invention, the linear phenolic epoxy resin is preferably purchased from Hunan Servi New Material Technology Co., Ltd., and its grade is R-0273. In this invention, the linear phenolic epoxy resin can improve the flexibility, chemical resistance, and boiling resistance of the coating.

[0061] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by this invention, by weight percentage, include 15-25% modified organosilicon resin, which can be 15%, 20%, or 25%. The modified organosilicon resin is the modified organosilicon resin prepared by the preparation method described in the above technical solutions. In this invention, the modified organosilicon resin is a dicyandiamide-curable organosilicon specialty resin, which, when combined with epoxy resin and linear phenolic epoxy resin, serves as the main film-forming substance of the coating, significantly improving the high-temperature resistance of the coating while retaining the excellent adhesion and chemical resistance of epoxy and phenolic resins.

[0062] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by this invention, by weight percentage, include 2-5% graphene-modified silicon-titanium nanopolymer slurry, which can be 2%, 3%, 4%, or 5%. In this invention, the graphene-modified silicon-titanium nanopolymer slurry comprises the following raw materials in parts by weight: 40-60 parts titanium hydride, 2-5 parts activated silica, 1-2 parts silane coupling agent-modified graphene, 10-30 parts silicon-modified epoxy resin, 3-6 parts reactive diluent, 2-10 parts N-methylpyrrolidone, 1-5 parts dispersant, 1-5 parts coupling agent, 0.01-0.1 parts catalyst, 0.1-0.2 parts wetting agent, and 0.1-0.2 parts wetting aid. The specific graphene-modified silicon-titanium nanopolymer slurry is described in Chinese Patent CN113416469A (application number 202110788222.4). In this invention, the modified graphene-silicon-titanium nanopolymer slurry can be cross-linked with dicyandiamide, and the resulting nano-polymer network structure is distributed inside the coating, mainly used to improve the overall density and impermeability of the coating.

[0063] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by this invention, by weight percentage, include 15-25% wear-resistant reinforcing filler, which can be 15%, 17%, 18%, 20%, or 25%. In this invention, the wear-resistant reinforcing filler includes carbides and / or metal oxides. The carbides preferably include one or more of silicon carbide, titanium carbide, and tungsten carbide, and the metal oxides preferably include zirconium oxide and / or ceramic alumina. When the wear-resistant reinforcing filler includes carbides and metal oxides, the mass ratio of the carbides to the metal oxides is preferably 1:2-2.4. In this invention, the particle size of the carbides is preferably 1250-3000 mesh, and the particle size of the metal oxides is preferably 1250-2000 mesh. In this invention, the silicon carbide mainly serves a wear-resistant function, while the metal oxides serve a wear-resistant and acid / alkali / salt corrosion-resistant function.

[0064] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by the present invention, by weight percentage, include 1-10% mica powder, which can be 1%, 5%, or 10%. In the present invention, the mica powder is preferably mica powder GA-4 (purchased from Anhui Gree New Material Technology Co., Ltd.); the mica powder has a flake structure, which improves the wear resistance of the coating while also improving its crack resistance and impermeability.

[0065] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by the present invention, by weight percentage, include 0.5% to 2% pigment, which can be 0.5%, 1%, or 2%. In the present invention, the pigment is preferably carbon black, which can be Cabot 660R; the pigment is used for color matching.

[0066] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by this invention, by weight percentage, include 0.1-0.3% of a hydrophobic interface modifier, which can be 0.1%, 0.2%, or 0.3%. In this invention, the hydrophobic interface modifier includes a fluorocarbon silane coupling agent and / or a modified polysiloxane copolymer. The fluorocarbon fluorosilane coupling agent preferably includes a heptadecafluorodecyltriethoxysilane coupling agent, and the modified polysiloxane copolymer preferably includes a polyether siloxane, which can be DIG 450. In this invention, the hydrophobic interface modifier can improve the hydrophobicity of the coating and reduce the penetration of water and ions from water.

[0067] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by the present invention, by weight percentage, include 0.1% to 1% fumed silica, which can be 0.1%, 0.2%, 0.5%, or 1%. In the present invention, the fumed silica is preferably fumed silica R974 (Degussa); the fumed silica gives the powder coating better flowability, making it easier to spray, while also helping to improve the hydrophobicity of the coating and providing anti-sagging properties.

[0068] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by the present invention, by weight percentage, include 5-15% silica powder, which can be 5%, 8%, 10%, or 15%. In the present invention, the particle size of the silica powder is preferably 1250-2000 mesh; the silica powder, as a wear-resistant filler, can reduce costs.

[0069] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by the present invention, by weight percentage, include 0.5% to 1.5% dispersant, which can be 0.5%, 1%, or 1.5%. In the present invention, the dispersant is preferably SA516 dispersant (Liuan Jietongda New Materials Co., Ltd.); the dispersant enables the powder to be dispersed more easily, stably, and quickly.

[0070] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by the present invention, by weight percentage, include 0.5% to 1.5% wetting agent, which can be 0.5%, 1%, 1.2%, or 1.5%. In the present invention, the wetting agent is preferably 701 wetting agent (Huangshan Jinfeng Industrial Co., Ltd.); the wetting agent helps to wet the powder during the coating production process, so that the dispersant is better distributed on the powder surface.

[0071] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by the present invention, by weight percentage, include 0.5% to 1.5% defoamer, which can be 0.5%, 1%, or 1.5%. In the embodiments of the present invention, the defoamer is preferably 542DG defoamer (Troy); the defoamer is used to release gas during coating curing and is not prone to generating bubbles within the coating.

[0072] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by the present invention, by weight percentage, include 0.4% to 1.5% conductive agent, which can be 0.4%, 0.5%, 1%, or 1.5%. In the present invention, the conductive agent is preferably conductive mica powder with a particle size of 5 to 20 micrometers; the conductive agent is used to improve the conductivity of the coating during electrostatic spraying, so that the coating can be better sprayed onto the workpiece.

[0073] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by the present invention include 0.5% to 1.5% adhesion promoter, which can be 0.5%, 1%, or 1.5% by weight. In the present invention, the adhesion promoter is preferably BYK-3942P.

[0074] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by the present invention, by weight percentage, include 0.5% to 1.5% leveling agent, which can be 0.5%, 1%, 1.2%, or 1.5%. In the present invention, the leveling agent is preferably PL-200 leveling agent (Estrom); the leveling agent can reduce the surface tension during the baking, curing, and melting of the coating, improve the leveling properties of the coating, and prevent the formation of uneven orange peel texture.

[0075] The raw materials for preparing the heavy-duty anti-corrosion powder coating provided by this invention, by weight percentage, include 1-5% dicyandiamide curing agent, which can be 2%, 3%, 4%, or 5%. In this invention, the dicyandiamide curing agent is preferably K7104 (modified dicyandiamide from Liuan Jietongda New Materials Co., Ltd.). In this invention, the dicyandiamide curing agent crosslinks with the resin, causing the coating to eventually cure.

[0076] In this invention, the particle size of the heavy-duty anti-corrosion powder coating is preferably less than 70 micrometers, and the mass percentage of particles with a particle size of less than 50 micrometers is ≥80%.

[0077] The heavy-duty anti-corrosion powder coating provided by this invention is an integrated wear-resistant and anti-corrosion coating with excellent interfacial bonding performance, enabling long-term protection under extreme working conditions (70MPa / 180℃ high pressure and high temperature test, ≥16h). In contrast, traditional epoxy powder coatings are prone to "bubbling-peeling" failure under 70MPa high pressure and 148℃ high temperature, and their insufficient wear resistance leads to severe wear on the inner wall of the pipeline (abrasion resistance ≤2.0L / μm by sand falling method), and the interfacial bonding strength between the coating and the substrate is low (adhesion ≤5A grade).

[0078] This invention provides a method for preparing the heavy-duty anti-corrosion powder coating described above, comprising the following steps:

[0079] Graphene-modified silicon-titanium nanopolymer slurry is premixed with a hydrophobic interface modifier to form a hydrophobic premixed slurry.

[0080] The hydrophobic premixed slurry is mixed with pigments and wear-resistant reinforcing fillers to form a core-shell structured slurry.

[0081] The core-shell structure slurry is mixed with epoxy resin, linear phenolic epoxy resin, modified organosilicon resin, mica powder, fumed silica, silica powder, dispersant, wetting agent, defoamer, conductive agent, adhesion promoter, leveling agent and dicyandiamide curing agent. The resulting mixture is melt-extruded and then powdered to obtain the heavy-duty anti-corrosion powder coating.

[0082] This invention premixes graphene-modified silicon-titanium nanopolymer slurry with a hydrophobic interface modifier to form a hydrophobic premixed slurry. In this invention, the coupling agent (such as an epoxy silane coupling agent) in the graphene-modified silicon-titanium nanopolymer slurry can undergo silanol condensation with the hydrophobic interface modifier (fluorocarbon silane coupling agent and / or modified polysiloxane copolymer). The graphene-modified silicon-titanium nanopolymer slurry contains solid particulate matter (silica and titanium hydride). The hydrophobic interface modifier migrates to the surface of the solid particles and couples with them, and also condenses with the silane coupling agent on the surface of the solid particles. This prevents the hydrophobic interface modifier from migrating but anchors it around the solid particles in the slurry. Therefore, the premixing process forms a hydrophobic coating layer. In this invention, the water contact angle of the coating surface after curing the hydrophobic premixed slurry with an amine curing agent for epoxy resin is ≥110°.

[0083] After obtaining the hydrophobic premixed slurry, the present invention mixes the hydrophobic premixed slurry with the wear-resistant reinforcing filler to form a core-shell structured slurry. In this invention, the mixing is preferably carried out in a high-speed disperser, with a preferred speed of 5000–8000 rpm (5000, 6000, 7000, or 8000 rpm), and a preferred mixing time of 15–20 min (15, 17, or 20 min). Because the graphene-modified silicon-titanium nanopolymer slurry contains resin (silicon-modified epoxy resin) and a large amount of coupling agent, which adsorbs and anchors to the surface of the solid wear-resistant reinforcing filler, a core-shell structure can be formed after the mixing process.

[0084] After obtaining the core-shell structure slurry, the present invention mixes the core-shell structure slurry with epoxy resin, linear phenolic epoxy resin, modified organosilicon resin, pigment, mica powder, fumed silica, silica powder, dispersant, wetting agent, defoamer, conductive agent, adhesion promoter, leveling agent and dicyandiamide curing agent, and then melt-extrudes the resulting mixture to obtain the heavy-duty anti-corrosion powder coating.

[0085] In this invention, the mixing is preferably high-speed dispersion mixing, the rotation speed of the high-speed dispersion mixing is preferably 1000-2000 rpm, which can be 1000, 15000 or 2000 rpm, and the time is preferably 20-60 min, which can be 20, 30, 40, 50 or 60 min.

[0086] In this invention, the melt extrusion is preferably a twin-screw extrusion, specifically carried out in a twin-screw extruder. Starting from the feed end, the twin-screw extruder is sequentially configured with zone I, zone II, and zone III. The temperature of zone I is preferably 95–110°C, and can be 95, 100, 105, or 110°C. The temperature of zone II is preferably 110–130°C, and can be 110, 120, or 130°C. The temperature of zone III is preferably 90–100°C, and can be 90, 95, or 100°C.

[0087] In this invention, the preferred method for powder preparation is to slice and crush the material after melt extrusion, and then sieve it; the sieving is preferably through a 200-mesh sieve.

[0088] This invention provides the application of the heavy-duty anti-corrosion powder coating described in the above technical solutions or the heavy-duty anti-corrosion powder coating prepared by the above technical solutions in the corrosion protection of oilfield pipelines.

[0089] The heavy-duty anti-corrosion powder coating provided by this invention is particularly suitable for long-term protection of oilfield pipelines under high temperature, high pressure and strong corrosion conditions, and has passed the authoritative testing and certification of the National Petroleum Pipeline Quality Inspection and Testing Center (CNPC).

[0090] In this invention, the preferred method of application is:

[0091] The oilfield pipelines are pre-treated and preheated.

[0092] The preheated oilfield pipeline is sprayed with the heavy-duty anti-corrosion powder coating and then cured.

[0093] In this invention, the pretreatment specifically involves sandblasting the oilfield pipeline to remove rust to Sa2.5–3 grade (steel grit particle size 0.8–1.2 mm), and the surface roughness Ra of the pretreated oilfield pipeline is preferably 35–75 μm. In this invention, the preheating temperature is preferably 180–220℃. In this invention, the preferred spraying parameters are: spray thickness: 0.35 ± 0.05 mm; rotation speed: 200–250 rpm; spray gun moving speed: 20–30 m / min; the preferred curing parameters are: temperature: 200–240℃; time: ≥30 min; rotational curing (to prevent sagging).

[0094] To further illustrate the present invention, the preparation method of the modified organosilicon resin and the heavy-duty anti-corrosion powder coating provided by the present invention, as well as their preparation method and application, are described in detail below with reference to examples. However, these should not be construed as limiting the scope of protection of the present invention.

[0095] Example 1

[0096] The raw materials and their mass fractions for preparing heavy-duty anti-corrosion powder coatings are shown in Table 1.

[0097] Table 1. Raw materials and mass fractions of each raw material for preparing heavy-duty anti-corrosion powder coatings.

[0098]

[0099]

[0100] The preparation steps of the modified organosilicon resin in Table 1 are as follows:

[0101] (1) Hydrolysis reaction: 70g of methyltrimethoxysilane (MTMS), 30g of phenyltriethoxysilane (PTES) and 20g of isocyanate-propyltriethoxysilane were added to a reaction vessel containing 100mL of ethanol-water (volume ratio of ethanol to water of 95:5) with pH=4.5, and stirred at 60℃ for 2h.

[0102] (2) Polycondensation modification: Add 15g of dicyandiamide and 8g of NH2-POSS (purchased from Xi'an Qiyue Biotechnology) to the product of step (1), heat to 80℃ and react for 3h, the viscosity of the system reaches 2500mPa·s.

[0103] (3) Solid powdering treatment: After vacuum desolventizing at 120℃, the modified organosilicon resin powder is obtained by pulverizing.

[0104] The preparation steps for heavy-duty anti-corrosion powder coatings are as follows:

[0105] (1) Primary dispersion: Graphene-modified silicon-titanium nanopolymer slurry is premixed with hydrophobic interface modifier to form hydrophobic premixed slurry (contact angle ≥110°);

[0106] (2) Secondary dispersion: The premixed slurry obtained in step (1) and the fillers (ceramic alumina and silicon carbide) are processed in a high-speed disperser (6000 rpm) for 20 min to form a core-shell structured slurry;

[0107] (3) Three-stage dispersion: After adding the remaining components to the material obtained in step (2), high-speed mixing and dispersion are carried out (speed 2000 rpm, processing time 40 min); then, the material is melt-extruded and pulverized by a twin-screw extruder with segmented temperature control (zone I 105℃ / zone II 120℃ / zone III 100℃), and sieved through a 200-mesh sieve. The powder coating particle size is less than 70 micrometers, and the mass ratio of particles with a particle size less than 50 micrometers is ≥80%.

[0108] Comparative Example 1

[0109] Omit TIGAR 450 from Table 1; the rest is the same as in Table 1. The preparation steps for the heavy-duty anti-corrosion powder coating are as follows (i.e., Comparative Example 1 does not undergo hydrophobic surface modification):

[0110] The graphene-modified silicon-titanium nanopolymer slurry, fillers (ceramic alumina and silicon carbide), and other remaining components were mixed and dispersed at high speed (2000 rpm, 40 min). Then, the mixture was melt-extruded and pulverized in a twin-screw extruder with segmented temperature control (zone I 105℃ / zone II 120℃ / zone III 100℃), and sieved through a 200-mesh sieve. The powder coating had a particle size of less than 70 micrometers, and the mass percentage of particles with a particle size of less than 50 micrometers was ≥80%.

[0111] The performance of the heavy-duty anti-corrosion powder coating prepared in Example 1 was tested (by CNPC, according to standard SY / T6717-2016), and the test results are as follows:

[0112] Appearance: Smooth, even, and free from defects such as bubbles, orange peel, and drips;

[0113] Dry film thickness: 277.5 μm;

[0114] No leaks were found.

[0115] Abrasion resistance: 2.2 L / μm (sandblasting method);

[0116] Adhesion: 5A grade (superior to the standard requirement of 3A grade);

[0117] Resistance to chemical corrosion:

[0118] 10% HCl (room temperature, 90 days): No change in coating.

[0119] 3.5% NaCl (room temperature, 90 days): No change in coating.

[0120] Crude oil (80℃, 90 days): No change in coating;

[0121] High temperature and high pressure performance:

[0122] Condition 1: Liquid phase: NaOH solution (pH=12.5) and H2SO4 solution (pH=2) were used at 180℃ / 70MPa / 16h, with the specimen completely immersed in the liquid and pressurized with gaseous N2; Condition 2: Liquid phase: a mixture of water, toluene and kerosene in equal volume ratio was used at 107℃ / 35MPa / 16h, with 2 / 3 of the specimen immersed in the liquid and pressurized with CO2; Under the above two conditions, the three test results showed that the coating had no bubbles and the adhesion remained at grade 5A.

[0123] Technical effects: Abrasion resistance improved by ≥26.7% (compared to the standard requirement of 2.0L / μm); adhesion improved by ≥66.7% (compared to the standard requirement of 3A grade); passed the 16-hour extreme working condition test (180℃ / 70MPa).

[0124] Figure 1 The images are electron microscope (EM) images (a) of a commercially available ordinary fusion-bonded epoxy powder coating after abrasion resistance testing and (b) of a heavy-duty anti-corrosion powder coating obtained in Comparative Example 1 after abrasion resistance testing. Figure 2 The images are: (a) Electron micrographs of a commercially available ordinary fusion-bonded epoxy powder coating after abrasion resistance testing, and (b) Electron micrographs of a heavy-duty anti-corrosion powder coating obtained by multi-stage dispersion in Example 1 after abrasion resistance testing. Figure 2 Ordinary fusion-bonded epoxy powder coatings and Figure 1The ordinary fusion-bonded epoxy powder coatings used in the process were purchased from different manufacturers. Figure 1 From this, we can know that Figure 1 (a) ratio Figure 1 The pigment particles inside the middle (b) coating are much larger, and Figure 1 (a) is far inferior to Figure 1 The middle (b) is dense, and the wear marks are also more obvious. Figure 2 In the middle, (a) has significantly larger and more numerous internal pores than (b), and the wear marks are more obvious. Figure 2 (b) Even if the observation multiple is Figure 1 and Figure 2 It is twice that of (a), but almost no aggregated solid particles are visible inside the coating, and the wear marks are minimal.

[0125] Figure 3 The appearance of the heavy-duty anti-corrosion powder coating obtained by multi-stage dispersion in Example 1 shows that the coating surface is smooth, uniform, and delicate.

[0126] The heavy-duty anti-corrosion powder coating prepared in Example 1 was subjected to high-temperature and high-pressure simulation test (refer to SY / T6717-2016) and compared with the traditional fusion-bonded epoxy coating. The test conditions and results are shown in Table 2.

[0127] Table 2 Results of High Temperature and High Pressure Simulation Tests

[0128]

[0129] Example 2

[0130] The raw materials and their mass fractions for the preparation of the heavy-duty anti-corrosion powder coating are shown in Table 3, and the rest are the same as in Example 1.

[0131] Table 3. Raw materials and mass fractions of each raw material for the preparation of heavy-duty anti-corrosion powder coatings.

[0132]

[0133] Example 3

[0134] The raw materials and their mass fractions for the preparation of the heavy-duty anti-corrosion powder coating are shown in Table 4, and the rest are the same as in Example 1.

[0135] Table 4. Raw materials and mass fractions of each raw material for the preparation of heavy-duty anti-corrosion powder coatings.

[0136]

[0137] The performance test results of the heavy-duty anti-corrosion powder coatings prepared in Examples 2 and 3 are shown in Table 5.

[0138] Table 5 Performance test results of the heavy-duty anti-corrosion powder coatings prepared in Examples 2-3

[0139]

[0140] As can be seen from the above embodiments, the heavy-duty anti-corrosion powder coating provided by the present invention is an integrated wear-resistant and anti-corrosion coating with excellent interfacial bonding performance, which can achieve long-term protection of the coating under extreme working conditions.

[0141] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a modified organosilicon resin, characterized in that, Includes the following steps: Methyltrimethoxysilane, phenyltriethoxysilane, and isocyanate-propyltriethoxysilane are mixed with an alcohol-water solvent and subjected to hydrolysis and polycondensation to obtain a solution containing terminal isocyanate-based polysiloxanes; the hydrolysis and polycondensation are carried out under conditions with a pH of 4.5-6; the alcohol in the alcohol-water solvent is ethanol, and the volume ratio of the alcohol to water is 95:5; The solution containing the terminal isocyanate polysiloxane was mixed with dicyandiamide and amino-entrained cage-type silsesquioxane to carry out a hybrid crosslinking polycondensation reaction to obtain a solution containing Si, O, C and N hybrid crosslinked polymers. The solvent is removed from the solution containing the Si, O, C and N hybrid crosslinked polymer to obtain the modified organosilicon resin; By mass fraction, the methyltrimethoxysilane comprises 60-80 parts, the phenyltriethoxysilane comprises 20-40 parts, the isocyanate-propyltriethoxysilane comprises 15-25 parts, the dicyandiamide comprises 10-20 parts, and the amino-coated cage-type silsesquioxane comprises 5-10 parts.

2. The preparation method according to claim 1, characterized in that, The hydrolysis condensation reaction is carried out at a temperature of 50-60°C for 2-4 hours; the hybrid crosslinking condensation reaction is carried out at a temperature of 60-100°C for 2-6 hours.

3. A heavy-duty anti-corrosion powder coating, characterized in that, The raw materials include the following ingredients in weight percentage: The composition includes: 15-35% epoxy resin, 5-15% linear phenolic epoxy resin, 15-25% modified silicone resin, 2-5% graphene-modified silicon-titanium nanopolymer slurry, 15-25% wear-resistant reinforcing filler, 1-10% mica powder, 0.5-2% pigment, 0.1-0.3% hydrophobic interface modifier, 0.1-1% fumed silica, 5-15% silica powder, 0.5-1.5% dispersant, 0.5-1.5% wetting agent, 0.5-1.5% defoamer, 0.4-1.5% conductive agent, 0.5-1.5% adhesion promoter, 0.5-1.5% leveling agent, and 1-5% dicyandiamide curing agent. The wear-resistant reinforcing filler includes carbides and / or metal oxides; the hydrophobic interface modifier includes fluorocarbon silane coupling agents and / or modified polysiloxane copolymers; the modified organosilicon resin is a modified organosilicon resin prepared by the preparation method according to any one of claims 1 to 2. The graphene-modified silicon-titanium nanopolymer slurry comprises the following raw materials in parts by weight: 40-60 parts of titanium hydride, 2-5 parts of activated silica, 1-2 parts of silane coupling agent-modified graphene, 10-30 parts of silicon-modified epoxy resin, 3-6 parts of reactive diluent, 2-10 parts of N-methylpyrrolidone, 1-5 parts of dispersant, 1-5 parts of coupling agent, 0.01-0.1 parts of catalyst, 0.1-0.2 parts of wetting agent, and 0.1-0.2 parts of wetting aid.

4. The heavy-duty anti-corrosion powder coating according to claim 3, characterized in that, The epoxy equivalent of the epoxy resin is 600~1800.

5. The heavy-duty anti-corrosion powder coating according to claim 3, characterized in that, The carbide includes one or more of silicon carbide, titanium carbide, and tungsten carbide; the metal oxide includes zirconium oxide and / or ceramic alumina.

6. The heavy-duty anti-corrosion powder coating according to claim 3, characterized in that, The fluorocarbon silane coupling agent includes heptadecafluorodecyltriethoxysilane, and the modified polysiloxane copolymer includes polyether siloxane.

7. The heavy-duty anti-corrosion powder coating according to any one of claims 3 to 6, characterized in that, The heavy-duty anti-corrosion powder coating has a particle size of less than 70 micrometers, and the mass percentage of particles with a particle size of less than 50 micrometers is ≥80%.

8. The method for preparing the heavy-duty anti-corrosion powder coating according to any one of claims 3 to 7, characterized in that, Includes the following steps: Graphene-modified silicon-titanium nanopolymer slurry is premixed with a hydrophobic interface modifier to form a hydrophobic premixed slurry. The hydrophobic premixed slurry is mixed with wear-resistant reinforcing filler to form a core-shell structured slurry. The core-shell structure slurry is mixed with epoxy resin, linear phenolic epoxy resin, modified organosilicon resin, pigment, mica powder, fumed silica, silica powder, dispersant, wetting agent, defoamer, conductive agent, adhesion promoter, leveling agent and dicyandiamide curing agent. The resulting mixture is melt-extruded and then powdered to obtain the heavy-duty anti-corrosion powder coating.

9. The application of the heavy-duty anti-corrosion powder coating according to any one of claims 3 to 7 or the heavy-duty anti-corrosion powder coating prepared by the preparation method according to claim 8 in the corrosion protection of oilfield pipelines.

Citation Information

Patent Citations

  • Graphene modified silicon-titanium nano polymer slurry as well as preparation method and application thereof

    CN113416469A

  • Preparation method of graphene modified silicon-titanium nano heavy anti-corrosion material

    CN111763437A

  • POSS (Polyhedral Oligomeric Silsesquioxane) modified polyurethane dispersion, preparation method thereof and nail polish containing POSS modified polyurethane dispersion

    CN115746234A